KERIS JAWA TENGAH SEBAGAI CINDERAMATA : Kontinuitas dan Perubahannya - Krishna Hutama (Jurnal Dimensi Seni Rupa dan Desain, 2003)
AbstractThis keris comes under the category of stabbing weapons. According to research made by experts, such stabbing weapons are found only in Southeast Asia, especially in the Archipelago. The Keris has achieved its present form and function after a suffiently long era of development. This evolutions has been in rhythm with development of culture as a whole aspecially in Java. Moreever, the keris in its use implicates a vast part of life